Cycling Futures - Johnson, Marilyn (University of Adelaide Press, 2015)
Australasian researchers, practitioners, policy makers and community members are engaged in a global discussion on the role of cycling in addressing these concerns. Contributors to this book report on and extend this discussion as they explore the insights generated locally and internationally on the past, present and future of cycling. The focus of the first half of the book is largely on the current engagement with cycling, challenges faced by existing and would-be cyclists and the issues cycling might address. The second half of the book is concerned with strategies and processes of change. Contributors working from different ontological positions reflect on changing socio-spatial relations to enable the broadest possible participation in cycling.'